أهمية اتخاذ القرارات لحلّ المشاكل في المنظمات الصحية - بورزاق, نادية (My University, 2020)
According to our important study in order to make decisions to solve issues of health organization we conducted a field study regarding the guarantee conditions of outbreak of new corona virus epidemics. Since we realised the epidemics a serious issue and a big threat that threatens against health organization, we have organized to proceed an analytical study of the problem in a practical way. To achieve acceptable results to solve the health organization problems, it requires active, scientific, and practical participation along with effective efforts and also it needs to hire senior managers and workers and even patients , in order to analyse and categorise them in a scientific and innovative manner, All mentioned characters and methods lead to find appropriate solutions, and to it prevents to recurrence and exacerbate problems to achieve best and most effective health services in society
دراسة تحليلية لتفش ي وباء كورونا المستجدّ في ولاية مستغانم
Keywords: Scientific style to solve problems- Decision making، Rational decision، Health information systems،Health strategic planning